1990
DOI: 10.1017/s0016672300035199
|View full text |Cite
|
Sign up to set email alerts
|

Illegitimate pairing of the X and Y chromosomes in Sxr mice

Abstract: X/Y male mice carrying the sex reversal factor, Sxr, on their Y chromosomes typically produce 4 classes of progeny (recombinant X/X Sxr male male and X/Y non-Sxr male male, and non-recombinant X/X female female and X/Y Sxr male male) in equal frequencies, these deriving from obligatory crossing over between the chromatids of the X and Y during meiosis. Here we show that X/Y males that, exceptionally, carry Sxr on their X chromosome, rather than their Y, produce fewer recombinants than expected. Cytological stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

1991
1991
1997
1997

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 14 publications
(29 reference statements)
2
11
0
Order By: Relevance
“…There was also one exceptional individual, a hemizygous Ta male, which proved on later analysis to be XSxr/O and so had not inherited a maternal X. Among the total progeny a divergence from a 1:1 ratio of pseudoautosomal recombinant X/X females relative to nonrecombinant X/XSxr males (170:262) was evident, as in previous studies (9,10), although this was somewhat less extreme (1:1.5, as opposed to 1:4 in ref. 10), perhaps reflecting the different origin of the Y chromosome.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…There was also one exceptional individual, a hemizygous Ta male, which proved on later analysis to be XSxr/O and so had not inherited a maternal X. Among the total progeny a divergence from a 1:1 ratio of pseudoautosomal recombinant X/X females relative to nonrecombinant X/XSxr males (170:262) was evident, as in previous studies (9,10), although this was somewhat less extreme (1:1.5, as opposed to 1:4 in ref. 10), perhaps reflecting the different origin of the Y chromosome.…”
Section: Resultssupporting
confidence: 78%
“…Analysis of Mbo I-digested RT-PCR products amplified using Sry primers showed that musculus-type transcripts were present in both XYYd' and XYYd2 testes (Fig. Sc) Yp-Sxr recombination in XSxr/Y males has been postulated to explain the unexpectedly low frequency of pseudoautosomal recombinants among their offspring (9). In the present study, 7 Yp-Sxr recombinants out of 192 offspring were retrieved, giving a frequency of 4%.…”
Section: Resultssupporting
confidence: 48%
See 1 more Smart Citation
“…1990). The composition of the dicentric chromatids in XSv' Y individuals indicated that the recombination event occurred within the dis tal region of both sex chromosomes, and thus Cattanach et al (1990) attributed the dicentric chromatids to either crossover error between parasynapsed pseudoautosomal regions or re combination between pseudoautosomal regions that were paired in an inverted fashion. The data from XY* males are consistent with inverted pairing and recombination, as the composition of the dicentric chromatids observed in three metaphase II pairs suggests that recombination occurs within X-Y* bivalents in which the centromeric end of the Y* chromo some is parasynapsed with the distal end of the X chromosome (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Evans et al (37) extended this hypothesis to suggest that a recombinational event between the X and Y chromosomes is a prerequisite for successful completion of male meiosis. Although the obligate recombination hypothesis is supported by data obtained from studies involving males carrying the Y* (12,39) or Sxr mutations (37,(40)(41)(42), this hypothesis needs to be critically tested with male mice carrying normal sex chromosomes.…”
Section: 5mentioning
confidence: 99%